2006
DOI: 10.1185/030079906x132389
|View full text |Cite
|
Sign up to set email alerts
|

The economic value of anti-IgE in severe persistent, IgE-mediated (allergic) asthma patients:adaptation of INNOVATE to Sweden

Abstract: Based on the model and the assumptions used, our results suggest that omalizumab provides cost offsets, improves quality of life and may have an attractive ICER in treating the severe allergic asthma population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 30 publications
3
68
0
3
Order By: Relevance
“…Indeed, cost-effectiveness analyses of omalizumab that accounted for responder status have shown that omalizumab is cost-effective in patients with severe persistent allergic asthma. 73,74 One analysis 73 applied data from the INNOVATE 49 study to Sweden as a reference country and calculated an incremental cost-effectiveness ratio (ICER) of €56,091, slightly higher than the Swedish accepted threshold of €53,384 (SEK 500,000). The annual cost of treatment with omalizumab, based on the dose distributions observed in INNOVATE was calculated to be €15,444.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Indeed, cost-effectiveness analyses of omalizumab that accounted for responder status have shown that omalizumab is cost-effective in patients with severe persistent allergic asthma. 73,74 One analysis 73 applied data from the INNOVATE 49 study to Sweden as a reference country and calculated an incremental cost-effectiveness ratio (ICER) of €56,091, slightly higher than the Swedish accepted threshold of €53,384 (SEK 500,000). The annual cost of treatment with omalizumab, based on the dose distributions observed in INNOVATE was calculated to be €15,444.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…The authors found that the ICER for omalizumab ranged between J27,739 and J40,840. This range was considerably lower than the ICER calculated by DEWILDE et al [66] and would suggest that omalizumab is cost-effective as an add-on therapy in patients with severe persistent asthma.…”
Section: Costs Associated With Omalizumabmentioning
confidence: 55%
“…DEWILDE et al [66] performed an economic evaluation of omalizumab, which was based on the data from the INNOVATE trial [41]. They found the incremental cost-effectiveness ratio (ICER), which is the difference in total costs between two treatment arms per quality-adjusted life year, for omalizumab as an add-on therapy to be J56,091.…”
Section: Costs Associated With Omalizumabmentioning
confidence: 99%
“…Eight studies compared monotherapy vs monotherapy (38,41,42,45,46,51,56,58). Four studies compared add-on omalizumab vs usual care (39,47,57,60). There was one study over the time period that considered the costs of reliever therapies, but since no health outcome was reported this study was excluded (62).…”
Section: Literature Search Resultsmentioning
confidence: 99%